Development of a data model to facilitate rapid watershed delineation. (December 2019) - Haag, Scott; Shokoufandeh, Ali
Abstract: An efficient model to store and retrieve watershed boundaries using graph-theoretic approaches is proposed. Our approach utilizes three algorithms and accepts as input standard Digital Elevation Model DEM derived flow direction grids (D8) or stream reach catchment boundaries and outputs derived watershed boundaries. This technique was applied to the ≈ 36, 000 km 2 Delaware River Watershed using the National Hydrography Plus Version 2 Dataset. This technique is showed to provide significant reductions in processing (98–99%), storage (81–82%), and retrieval complexity (95–96%) for polygons and (80–86%) for nodes when compared to existing and hypothetical data models that are used to create watershed boundaries. Highlights: A data model to allow the creation of watersheds for any location is proposed. This technique reduces the processing by ~99%, storage by ~82%, and retrieval by ~96% for polygons and by ~86% for nodes. The proposed data model provides equivalent results to existing functions (eg TAUDEM's gauge watershed). The proposed model can be created in linear time as a function of the flow direction grid or polygonal catchment boundaries.